Dengue with signs of alarm and Leptospirosis in a pediatric patient with COVID-19: Dengue con signos de alarma y Leptospirosis en un paciente pediátrico con COVID-19 - Nakandakari Gomez, Mayron David (2021)
Dengue and Leptospirosis are endemic metaxenic diseases that affect tropical and subtropical areas, mostly in underdeveloped countries. In addition to this, the COVID-19 pandemic is causing a great deal of damage to both the population and the health level. This is the case of a 13-year-old patient who had fever, gingival and intermenstrual bleeding, abdominal pain and shortness of breath. She had SARS-CoV-2 IgM and IgG positive rapid test, and positive serology NS1 for Dengue and IgM for Leptospira. In addition, non-contrast pulmonary tomography showed areas of consolidated and frosted glass at the base level, as well as cysturitis. Diagnoses of COVID-19 pneumonia, Dengue with warning signs and Leptospirosis were had. Therapeutics were based on fluid therapy according to diuresis and blood pressure, symptomatic, oxygen support, constant monitoring and antibiotic therapy with Ceftriaxone, having a favorable evolution.